2015
DOI: 10.1111/nicc.12199
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness trajectory for patients, families and nurses – a literature review

Abstract: Critical care nurses can and should play a role in preparing and supporting patients and families beyond the critical care unit. In turn, Registered Nurses needed to be supported to fulfil this important role in enabling the process of moving patients and their families from surviving to thriving (survivorship).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Our data suggest that delaying the transition from EN to PO only until a patient can demonstrate the ability to consume adequate nutrition orally may effectively enhance nutrition intake in this population. Successful LMV and transition from the ICU to ward marks a significant point in the trajectory of critical illness 28 and the beginning of the journey to recovery. Although no formal guidelines for transitioning patients from EN to an oral diet exist specifically for the recovering critically ill, Massanet et al 29 propose permanent discontinuation of EN only when a patient has demonstrated the ability to consume >75% of daily caloric needs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that delaying the transition from EN to PO only until a patient can demonstrate the ability to consume adequate nutrition orally may effectively enhance nutrition intake in this population. Successful LMV and transition from the ICU to ward marks a significant point in the trajectory of critical illness 28 and the beginning of the journey to recovery. Although no formal guidelines for transitioning patients from EN to an oral diet exist specifically for the recovering critically ill, Massanet et al 29 propose permanent discontinuation of EN only when a patient has demonstrated the ability to consume >75% of daily caloric needs.…”
Section: Discussionmentioning
confidence: 99%
“…The environment in which men live may not be conducive to long‐term discharge care. Prior research has shown that survivors of critical illnesses need to experience dynamic interplay when endeavoring to readjust to life after critical care, and that family members could be good interpersonal and societal stimulators (Page, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the dominant focus on medical disease perspective in acute illness and hospital systems, new models of care directed toward understanding the relationships of professional practice and human science are being advanced (Brewer & Watson, 2015;Stimpfel et al, 2014;Weyant et al, 2017). In particular, nursing care with an approach of understanding the human experience (Page, 2016) can be enhanced by incorporating narratives (van Manen, 2017). Developing and refining methods to help nurses gain understanding of the experiences of nursing care of families during an acute illness may be the catalyst for a change in their practice of interacting with families (Ellis et al, 2016).…”
Section: Gaining Understandings Through Narrativesmentioning
confidence: 99%